2014
DOI: 10.1016/j.mhpa.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Regular aerobic exercise increases dispositional mindfulness in men: A randomized controlled trial

Abstract: Dispositional mindfulness is a construct described as the propensity to be aware of one's actions in everyday life. Although high dispositional mindfulness has been demonstrated to be beneficial for improved mental and physical health, little is known about ways to improve dispositional mindfulness for individuals not practicing meditation or mindful exercises. The study aimed at investigating (1) whether dispositional mindfulness can also be trained by regular aerobic exercise and (2) whether changes in dispo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…For example, there is evidence that exercise, such as included in HEP, may have an impact on what we measure as mindfulness. Mothes et al [67] demonstrated that regular aerobic exercise can increase measures of dispositional mindfulness, using the Mindfulness Attention Awareness Scale [68]. Such findings point to the importance of refining our definitions of mindfulness and being aware of how well they match the sample being investigated [69] ; i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is evidence that exercise, such as included in HEP, may have an impact on what we measure as mindfulness. Mothes et al [67] demonstrated that regular aerobic exercise can increase measures of dispositional mindfulness, using the Mindfulness Attention Awareness Scale [68]. Such findings point to the importance of refining our definitions of mindfulness and being aware of how well they match the sample being investigated [69] ; i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Higher state mindfulness during physical activity should result in higher satisfaction with physical activity and thus reinforce physical activity (Tsafou et al, 2016;Tsafou, Lacroix, van Ee, Vinkers, & De Ridder, 2017). It may also be that physical activity increases trait mindfulness (Mothes, Klaperski, Seelig, Schmidt, & Fuchs, 2014;Shelov, Suchday, & Friedberg, 2009). Finally, mindfulness may influence the relation between motivation to engage in physical activity and physical activity behaviour (Brown & Ryan, 2003;Ryan & Deci, 1985).…”
Section: Behavioural Domainsmentioning
confidence: 99%
“…Regular physical exercise decreases symptoms of anxiety and depression (Conn 2010a; Conn 2010b; McDonald and Hodgdon 1991), as well as psychological stress and anger (Hassmén et al 2000); counters an over reactive stress-response system; and reduces rumination (Mothes et al 2014). Physical exercise gives energy and at the same time promotes relaxation and better sleep (DiLorenzo et al 1999; Youngstedt et al 1997), boosts the immune system (LaPerriere et al 1990), and enhances cognitive and executive functioning as well as positive affect (Reed and Buck 2009).…”
Section: Introductionmentioning
confidence: 99%